Novel Bat Influenza Virus NS1 Proteins Bind Double-Stranded RNA and Antagonize Host Innate Immunity - Turkington, Hannah L. (J Virol, 2015)
We demonstrate that novel bat HL17NL10 and HL18NL11 influenza virus NS1 proteins are effective interferon antagonists but do not block general host gene expression. Solving the RNA-binding domain structures revealed the canonical NS1 symmetrical homodimer, and RNA binding required conserved basic residues in this domain. Interferon antagonism was strictly dependent on RNA binding, and chimeric bat influenza viruses expressing NS1s defective in this activity were highly attenuated in interferon-competent cells but not in cells unable to establish antiviral immunity.